Cardiac hydatidosis: a follow-up with cardiovascular magnetic resonance - Braggion-Santos, Maria F.; Abdel-Aty, Hassan; Hofmann, Nina; Katus, Hugo; Steen, Henning (Circulation, 2012)
We present a case of a 38-year-old Turkish patient with a previously diagnosed cardiac hydatidosis, which is a parasitic infection most commonly induced by Echinococcus granulosus and with only rare cardiac involvement (0.5%-2.0%). In 1998, the patient survived a cardiogenic shock caused by the rupture of 1 hydatic cyst and concomitant cardiac tamponade. Postsurgery, the patient was treated pharmacologically with albendazole. In 2006, a cardiac magnetic resonance and a computed tomography examination showed recurrent myocardial cystic formations (Figure 1). Disadvantageously, the largest cyst was located in the inferior wall of the left ventricle in close vicinity to the mitral valvular apparatus. An interdisciplinary conference came to the conclusion to neither treat the patient surgically, because of an extensive myocardial and perivalvular defect, nor pharmacologically with albendazole, because even anthelmintic medical intervention …